Representation of selected‐reaction monitoring data in the mzQuantML data standard. Issue 15 (5th June 2015) - Qi, Da; Lawless, Craig; Teleman, Johan; Levander, Fredrik; Holman, Stephen W.; Hubbard, Simon; Jones, Andrew R.
<x xml:space="preserve">Abstract</x> The mzQuantML data standard was designed to capture the output of quantitative software in proteomics, to support submissions to public repositories, development of visualization software and pipeline/modular approaches. The standard is designed around a common core that can be extended to support particular types of technique through the release of semantic rules that are checked by validation software. The first release of mzQuantML supported four quantitative proteomics techniques via four sets of semantic rules: (i) intensity‐based (MS1) label free, (ii) MS1 label‐based (such as SILAC or N15), (iii) MS2 tag‐based (iTRAQ or tandem mass tags), and (iv) spectral counting. We present an update to mzQuantML for supporting SRM techniques. The update includes representing the quantitative measurements, and associated meta‐data, for SRM transitions, the mechanism for inferring peptide‐level or protein‐level quantitative values, and support for both label‐based or label‐free SRM protocols, through the creation of semantic rules and controlled vocabulary terms. We have updated the specification document for mzQuantML (version 1.0.1) and the mzQuantML validator to ensure that consistent files are produced by different exporters. We also report the capabilities for production of mzQuantML files from popular SRM software packages, such as Skyline and Anubis.